2017
DOI: 10.1002/cssc.201701314
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Sulfur‐Doped Copper Catalysts for the Selective Electroreduction of Carbon Dioxide to Formate

Abstract: The selective electroreduction of CO2 to formate (or formic acid) is of great interest in the field of renewable‐energy utilization. In this work, we designed a sulfur‐doped Cu2O‐derived Cu catalyst and showed that the presence of sulfur can tune the selectivity of Cu significantly from the production of various CO2 reduction products to almost exclusively formate. Sulfur is doped into the Cu catalysts by dipping the Cu substrates into ammonium polysulfide solutions. Catalyst films with the highest sulfur cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 48 publications
(124 reference statements)
4
84
1
Order By: Relevance
“…However, there are still many problems to be addressed, such as competition with hydrogen evolution reaction (HER) and low selectivity towards a desired product. Experimental and theoretical studies have revealed that the selectivity of Cu can be tuned by introducing a secondary component, such as indium (In), tin (Sn) and sulfur (S) [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still many problems to be addressed, such as competition with hydrogen evolution reaction (HER) and low selectivity towards a desired product. Experimental and theoretical studies have revealed that the selectivity of Cu can be tuned by introducing a secondary component, such as indium (In), tin (Sn) and sulfur (S) [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[2] The emergence of synergistic effects in multicomponent systems provides unique opportunities to overcome the scaling relation [3,4] between the binding energieso fi ntermediates inherently limiting the performance of transition metals typically used for this reaction. [5,6] However, al imited understanding of interfacial effects frequently accompanied by deep compositional and/or structural changes under reactionc onditions [7][8][9][10][11] precludes the derivationo fa ccurate structure-performancer elationships that can guide the optimization toward breakthrough advances.…”
Section: Introductionmentioning
confidence: 99%
“…As the amount of passed charge increases, CoS x phase reconstruction by ED‐CE with Cu ions further proceeds, as evidenced by the gradually attenuated Raman signals (Figure b) at 680, 612, 518, and 192 cm −1 , corresponding to CoO x and Co(OH) 2 (air oxidized CoS x ) . The broad Raman peak at 240–400 cm −1 , previously assigned to the vibrational mode of metal–S stretching (≈352 cm −1 for Co−S in CoS 2 and ≈296 cm −1 for Cu−S in Cu 2 S), remains but exhibits a slight redshift, suggesting the weakening of Co−S bonds in the CoS x templates, and further indicating the gradual replacement of Co ions in the CoS x matrix by the Cu 2+ ions in solution …”
Section: Resultsmentioning
confidence: 87%